Separation of mononuclear cells and identification of B lymphocytes: A comprehensive experiment for medical students. Issue 3 (5th March 2020) - Li, Jiao; Gao, Furong; Jin, Caixia; Shi, Xiujuan; Zhang, Chen; Jia, Song; Xu, Jie; Lv, Lixia; Yang, Wenzhuo; Xu, Lei
Abstract: In teaching of experiments for medical students, by using the isolation of mononuclear cells and identification of B lymphocytes, an experiment was developed that integrated biochemistry, cytology, and immunology techniques, from which the students performed a series of operations including spleen separation, isolating mononuclear cells, and identifying B lymphocytes. From the immunocytochemistry detection, we included advanced equipment—a flow cytometer—in the experiment, which detected the B lymphocytes more accurately. Moreover, we applied modern information technology to the teaching of experiments by using an internet study platform, micro‐lectures, and adopting "formative teaching and evaluation." This lab practice aims to increase the ability of medical students to solve problems using flexible scientific methods, to initiate them thinking about clinical and research application.